Risk factor for cerebrospinal fluid leak after endoscopic endonasal skull base surgery: a single-center experience. (1st June 2021) - Ozawa, Hiroyuki; Sekimizu, Mariko; Saito, Shin; Nakamura, Shintaro; Mikoshiba, Takuya; Watanabe, Yoshihiro; Ikari, Yuichi; Toda, Masahiro; Ogawa, Kaoru
Abstract: Background: One of the major complications in endoscopic endonasal skull base surgery (EESBS) is postoperative cerebrospinal fluid (CSF) leaks. Recently, EESBS has been applied to various skull base diseases as well as more complicated cases influenced by previous treatment with or without various comorbidities. Aims/objectives: This study aimed to assess the factors that influence the results of postoperative CSF leak after EESBS with mixed patient backgrounds. Materials and methods: We conducted a retrospective analysis of the clinical records of patients undergoing EESBS in our institution from 2012 to 2017. Results: Out of a total of 230 cases of EESBS, 11 (4.8%) suffered from postoperative CSF leakage. The rate of CSF leakage for pituitary adenoma, Rathke's cleft cyst, chordoma, and meningioma was 3.5%, 0%, 3.6% and 8.0%, respectively. Multiple variate analysis revealed that repeated surgery ( p = .008) and intraoperative CSF leak ( p = .044) were significant risk factors for postoperative CSF leakage. Conclusions and significance: The rate of postoperative CSF leakage in this study was comparable to previous reports, and repeated surgery may increase postoperative CSF leakage. The surgical strategy for tumor removal as well as skull base reconstruction should be given careful consideration according to tumor pathology and the patient's condition.